ANALYSIS OF THE EFFECTIVENESS OF CIVIC EDUCATION LEARNING BY USING THE WHATSAPP OF STUDENTS ON SMAN 1 KUOK KAMPAR, 2021-2020 - Rifka Rahma Yani; Gimin; Supentri (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
The distance education system is one of the solutions to overcome difficulties in face-to-face learning. WhatsApp is a social media that is used as a means of sending educational stimuli virtually (Learning Platform). This research was conducted to determine the effectiveness of Civics learning using WhatsApp. The formulation of the research problem is